Professional competencies, motivation, cognitive abilities and personality in pre-service teachers - Ballová Mikušková, Eva; Verešová, Marcela; Gatial, Viktor; Badošek, Radim; Kimplová, Tereza (Frontiers in Education, 2025)
The main aim of the study was twofold: to measure the personality traits, motivation to study, cognitive abilities and professional competencies of pre-service teachers from the Czech Republic and Slovakia and to examine their mutual relationships. A total of 515 pre-service teachers (194 Czechs, 321 Slovaks) aged 17–37 (M = 20.40; SD = 1.74; 21% men) filled out the Executive Skills Questionnaire-Revised, the Questionnaire on Teacher Interaction – Self-assessment, the Cognitive Reflection Test, the Didactic Competencies Questionnaire, the Scientific Reasoning Scale, the Slovak Teaching Style Questionnaire, the Scale of Motivation for Choosing Teaching Profession and the Big Five Inventory. Significant differences between Slovak and Czech pre-service teachers were identified in their motivation for choosing the teaching profession, cognitive abilities and executive functions and personality traits. Personality traits (agreeableness, negative emotionality and open-mindedness) and motivation for choosing the teaching profession (prosocial behavior, interest) were factors more strongly associated with professional competencies than country.